The Analogical Rationality in Science - Rengifo-Castañeda, Carlos-Adolfo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The most important result of Evandro Agazzi’s philosophy of science is probably the elaboration of an analogical concept of science in the sense that, after having characterized science as rigorous and objective knowledge, has shown that these two requirements are satisfied differently according to the epistemic, ontological and pragmatic terms of the inquiry, giving rise to the different natural and human or social sciences. The present article deepens this approach and underscores that every science is characterized by its own form of rationality. Therefore, the very concept of scientific rationality has an analogical sense according to the same conditions. Moreover, analogy concerns rationality as such and in such a way permits to avoid dogmatism, that pretends to accept just one form of rationality, as well as relativism, that does not recognize any form of rationality. As an introduction to this analysis, a presentation is offered of the fundamental characteristics of analogy according to its classical and contemporary theorizations, and then these requirements are applied to rationality and the concept of analogical rationality is presented.